Pendidikan Perencanaan Menjelang Era Asia-Pasifik: Perlunya Fleksibilitas Pendidikan - Pradono, . (Journal of Regional and City Planning, 1996)
Globalization in economy has resulted in economic interdependency on a global scale. Economic activities have experienced tertiary proc ess, or activities characterized by the domination  of  service sector activities. Eventhough this phenomenon is more intensive in  developed  countries,  its  implications,  nonetheless,  will  affect  the  developing countries.  At  a  certain  level  developing  countries  will  play  and  experience  this  new pattern.  Developing  countries  should  seize  this  momentum  rightly  .  Human  resources preparation  through education  is  very  essential  in  utilizing  this  momentum.  Planning education is one important area in responding to  the changing world. Some adjustments with new rethoric in education world is needed.